Ensino e aprendizagem de língua espanhola: a motivação de adolescentes de um Centro de Estudos de Línguas - Bellini, Mariana Bezerra (Universidade Federal de São Carlos, 2018)
Motivation is considered an important variable in the process of learning a foreign language. The nature of students' motivation is complex and variable, and can be influenced by internal factors, specific to the learner, and external factors related to their school context. In this scenario, we consider that actions of the teachers can favor the motivation of the students during the class. We established as objectives of this research: to investigate how motivational strategies can be applied in the Spanish classes and to analyze how the teacher can contribute to promote and/or maintain the motivation of the students. This work is based on the concepts of motivation in foreign language learning (PINTRICH and SCHUNK, 1996; GARDNER, 2001 and DÖRNYEI and OTTÓ, 1998). It is also based on the concept of motivational strategies in language classes (DÖRNYEI, 2001). This is a qualitative research and was carried out based on the action-research methodology. The data were generated in a Center of Language Studies in the State of São Paulo and the participants were 08 students of Spanish as a foreign language and their teacher who is also the researcher. The following instruments were used to produce the data: questionnaire, student-participant and teacher-researcher diaries. The results show a number of factors that influence the students' motivation.
Enseñanza y motivación de lengua española: la motivación de adolescentes de un Centro de Estudios de Lenguas
Keywords: Motivação; Ensino; Aprendizagem; Língua espanhola; Estratégias motivacionais; Motivación; Enseñanza; Aprendizaje; Lengua española; Estrategias motivacionales; LINGUISTICA, LETRAS E ARTES::LINGUISTICA